Compensation Management In Educational Institutions Teaching The Qur'an - Tarwin Tarwin (Peneliti.net, 2022)
Compensation is the most important part of managing human resources in a profit or non-profit institution. Because compensation practices have a significant impact on the performance and productivity of employees in particular and for institutions in general. The better the management of compensation, the better the performance of employees, conversely if the management of compensation is worse, the performance and productivity of employees will also be worse. The implementation of compensation management in educational institutions that teach the Qur'an in the South Tangerang area in general still does not meet the principles of fairness and decency. In addition, there is still no clear career path and has not received serious attention from the Institute. This can be seen from the inadequate amount of salary, allowances, facilities received by employees or teachers of the Qur'an and unclear career paths